2020
DOI: 10.1002/cbin.11474
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and prognosis potential of four gene promoter hypermethylation in prostate cancer

Abstract: The current prostate special antigen (PSA) test causes the overtreatment of indolent prostate cancer (PCa). It also increases the risk of delayed treatment of aggressive PCa. DNA methylation aberrations are important events for gene expression dysregulation during tumorigenesis and have been suggested as novel candidate biomarkers for PCa. This may improve the diagnosis and prognosis of PCa. This study assessed the differential methylation and messenger RNA (mRNA) expression between normal and PCa samples. Cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…ANXA2 showed a high diagnostic efficacy in 12 types of cancer, including CHOL, GBM, KICH, KIRP, LIHC, OV, PAAD, PRAD, READ, STAD, TGCT and THYM. Consistently with our findings, previous studies demonstrated a diagnostic value of ANXA2 in LIHC ( Zhang et al, 2012b ), PAAD ( Zhang et al, 2022 ) and PRAD ( Li et al, 2021 ). In the survival analysis, the expression of ANXA2 correlated with OS, PFI and DSS in several types of tumors.…”
Section: Discussionsupporting
confidence: 93%
“…ANXA2 showed a high diagnostic efficacy in 12 types of cancer, including CHOL, GBM, KICH, KIRP, LIHC, OV, PAAD, PRAD, READ, STAD, TGCT and THYM. Consistently with our findings, previous studies demonstrated a diagnostic value of ANXA2 in LIHC ( Zhang et al, 2012b ), PAAD ( Zhang et al, 2022 ) and PRAD ( Li et al, 2021 ). In the survival analysis, the expression of ANXA2 correlated with OS, PFI and DSS in several types of tumors.…”
Section: Discussionsupporting
confidence: 93%
“…It was also suggested that methylation of GSTM2 significantly correlated with the prognosis of PCa (Angulo et al, 2016). HAAO, which has been reported as the specific methylation biomarker for PCa, presented accurate discrimination between PCa and normal control samples and significantly prognostic implications (Li et al, 2021;Litovkin et al, 2014;Mahapatra et al, 2012;Li et al, 2021;Litovkin et al, 2014;Mahapatra et al, 2012). CYP27A1, which is a P450 enzyme catalyzing androgenanabolism, was suggested to be regulated by both genetic and epigenetic processes in PCa (Maksymchuk and Kashuba, 2020).…”
Section: Discussionmentioning
confidence: 95%
“…Moreover, HR mutations were also associated with several epigenetics and transcriptomics driven events, including SSX1, KCNE3, KLHDC7A, CDR2L methylations and F11, PSG4, AC129926.1 abnormal expression. Brie y, SSX1 is an epigenetic target that give rise to the disturbances of interacting multiprotein complexes such as the SWItch/Sucrose Non-Fermentable (SWI/SNF) complex in synovial sarcomas [48]; the hypermethylation of KCNE3 promoter is reported to be a diagnostic and prognostic biomarker in prostate cancer [49]; CDR2 is the main antigen for the onconeural antibody Yo, which is strongly associated with ovarian cancer [50]. It is notable that the role of KLHDC7A, F11, PSG4, and AC129926.1 have not previously been reported in cancers, and thus requires further exploration.…”
Section: Discussionmentioning
confidence: 99%